2018
DOI: 10.1097/qmh.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Framework for Weighting Panels Across Primary Care Disciplines: Findings From a Large US Multidisciplinary Group Practice

Abstract: Background:Health system redesign necessitates understanding patient population characteristics, yet many primary care physicians are unable to identify patients on their panel. Moreover, accounting for differential workload due to patient variation is challenging. We describe development and application of a utilization-based weighting system accounting for patient complexity using sociodemographic factors within primary care at a large multidisciplinary group practice.Methods:A retrospective observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Title and abstract review identified 294 potentially relevant articles that underwent full text review, with 74 including relevant data. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Title and abstract review identified 294 potentially relevant articles that underwent full text review, with 74 including relevant data. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows the findings for rules for adding and removing patients from panels and the frequency of updating panel lists as reported by 29 different health care systems and 5 empanelment guides. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 Details for each system or guide is provided in eTable 2 in the Supplement . Most organizations (29 [85.3%]) added patients to panels after 1 or more visits to primary care occurred (24 [70.6%] after 1 visit and 5 [14.8%] after several).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations